Unveiling the Driving Forces: Exploring Motivation and Influencing Factors in Research Publication Decisions - Rao, Mahendra Singh; Rao, Monica (DESIDOC Journal of Library & Information Technology, 2025)
This study investigates the motivations and influencing factors behind researchers’ decisions to publish their findings. A survey was conducted with 278 researchers across various disciplines using the Krejcie and Morgan13 sample size table to determine a representative sample. Statistical methods were employed to analyse factors such as academic recognition, career advancement, funding requirements, and personal satisfaction. The results indicate that while academic recognition and career advancement are significant motivators, personal satisfaction plays a crucial role. These findings offer insights for policymakers, funding agencies, and academic institutions aiming to support and incentivize research publication, thereby fostering a vibrant academic community.